God’s Revelation in the Holy Scriptures and the Quran - Modras, Krzysztof (Roczniki Kulturoznawcze, 2011)
The Holy Scriptures are a common element in many religions. They are the human embodiment of God's Word, which became a meeting place between God and man. Through it, God speaks to men, and they praise Him with His words in the community. For man will return to the original unity of one nation united under one God. God spoke in many ways in the history of men and all the revelations originate from one primitive source, which is the wisdom of God the Creator. Finally the revelation received its last and most perfect and universal form. For its transmission, God chose his messengers as intermediaries between Him and the people. They showed man the way to salvation and good conduct, they taught him the proper way of giving glory to God and revealed to him His will. The Scriptures were God's criterion for distinguishing right from wrong and truth from falsehood. It was the good news of the reward for a good life and a warning of punishment for wrong action. Human history become in the Scriptures an instructive moral lesson to be properly read.